The influence of 2 kbar pressure on the global and internal dynamics of human hemoglobin observed by quasielastic neutron scattering - Appavou, Marie-Sousai; Busch, Sebastian; Doster, Wolfgang; Gaspar, A. M.; Unruh, Tobias (European Biophysics Journal, 2011)
Pressure is a ubiquitous physical parameter in life and is commonly used in the life sciences to study new protein folding pathways or association-dissociation phenomena. In this paper, an investigation of the influence of pressure on hemoglobin, a multimeric protein, at the picosecond time scale is presented using time-of-flight neutron scattering. The aim is to observe the influence of pressure on the translational diffusion and internal motions of hemoglobin in a concentrated solution and a possible dissociation of the subunits as suggested by Pin et al. (Biochemistry 29:9194, 1990) using fluorescence spectroscopy. A new flat 2 kbar pressure cell made of an aluminum alloy has been used, which allowed the effect of pressure to be studied with minimum background contribution. Within this range of pressure, the effect of this physical parameter on global diffusion can be explained in terms of the change in the water buffer viscosity and an oligomerization of hemoglobin subunits, whereas the internal motions were less affected.
Keywords: Pressure; Protein; Hemoglobin; Dynamics; Quasielastic neutron scattering